Targeted Delivery of Amantadine-loaded Methacrylate Nanosphere-ligands for the Potential Treatment of Amyotrophic Lateral Sclerosis - Zamanzima Mazibuko; Sunaina Indermun; Mershen Govender; Pradeep Kumar; Lisa C du Toit; Yahya E Choonara; Girish Modi; Dinesh Naidoo; Viness Pillay (Frontiers Media S.A., 2018)
Purpose. This study aimed to develop and analyse poly(DL-lactic acid)-methacrylic acid nanospheres bound to the chelating ligand diethylenetriaminepentaacetic acid (DTPA)  for the targeted delivery of amantadine in Amyotrophic Lateral Sclerosis (ALS). Methods. The nanospheres were prepared by a double emulsion solvent evaporation technique statistically optimized employing a 3-Factor Box-Behnken experimental design. Analysis of the particle size, zeta potential, polydispersity (Pdl), morphology, drug entrapment and drug release kinetics were carried out. Results. The prepared nanospheres were determined to have particle sizes ranging from 68.31 to 113.6 nm (Pdl ≤ 0.5). An initial burst release (50% of amantadine released in 24 hr) was also obtained, followed by a prolonged release phase of amantadine over 72 hr. Successful conjugation of the chelating ligand onto the surface of the optimised nanospheres was thereafter achieved and confirmed by TEM. The synthesized modified nanospheres were spherical in shape, 105.6 nm in size, with a PdI of 0.24 and zeta potential of -28.0 mV. Conjugation efficiency was determined to be 74%. In vitro and ex vivo cell study results confirmed the intracellular uptake of the modified nanospheres by the NSC-34 cell line and the non-cytotoxicity of the synthesized nanospheres. Conclusions. Biocompatible amantadine-loaded nanospheres were successfully designed, characterized and optimized employing the randomized Box-Behnken statistical design. Delivery of amantadine over 72 hrs was achieved, with the nanospheres being of a size capable of internalization by the NSC- 34 cells.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.